THE OLDEST TISSUE DIFFERENTIATION IN PRECAMBRIAN (VENDIAN) ALGAE - Gnilovskaya M.B. (My University, 2003)
The earliest type of tissue differentiation in carbonaceous thallus has been discovered in the uniquely preserved material from the Vendian of the White Sea area (Russia). A new genus, Archyfasma gen. nov., with its type species A. dimera sp. nov. are described. The thallus of this species is composed of two types of tissue; the cortex with small parenchymatous cells and large verrucose structures on the cortex surface and the longitudinally fibrous medulla. Such complex anatomy resembles that of modern advanced red and brown algae and allows one to designate a new order, Archyfasmales ordo nov. The data obtained evidently prove the existence of tissue multicellularity in the Vendian that was earlier assumed by the author for vendotaenian algae.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский